2017
DOI: 10.1016/j.homp.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Informing the homeopathic practice for Turkish pharmacists: reviewing the example of Portuguese community pharmacies

Abstract: Portuguese pharmacists' attitudes towards their homeopathic practices highlighted the key elements for success in a field that is usually distant from traditional pharmaceutical education and practice. The present findings provide guidance for Turkish pharmacists willing to expand their professional scope and to embrace complementary medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Searches identified a total of 1695 items, of which 1385 were unique, and 1272 titles and abstracts were eliminated, leaving 113 full-text articles for further review. Of those, 94 were deemed ineligible, because they did not include qualitative data (n = 89), were conference abstracts (n = 3) or were irretrievable (n = 2), leaving a total of 19 articles that were included in this qualitative systematic review [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. A PRISMA diagram can be found in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Searches identified a total of 1695 items, of which 1385 were unique, and 1272 titles and abstracts were eliminated, leaving 113 full-text articles for further review. Of those, 94 were deemed ineligible, because they did not include qualitative data (n = 89), were conference abstracts (n = 3) or were irretrievable (n = 2), leaving a total of 19 articles that were included in this qualitative systematic review [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. A PRISMA diagram can be found in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…Many studies found that pharmacists' education fell short of providing them with a thorough understanding of DHSs [30,31,33,34,37,39,[41][42][43]. While some pharmacists expressed that they lacked a DHS education component in their pharmacy curricula [32,35,43], those that did receive training stated that they were not confident about their DHS knowledge [42,43].…”
Section: Theme 1: Challenges To Dhs Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…In another remarkable example of cultural crossfertilisation, a Portuguese-Turkish team led by Afonso Miguel Cavaco of Lisbon University, Portugal, working with colleagues from the University of Ankara, Turkey conducted a qualitative study of Portuguese pharmacists who use homeopathy, with a view to informing colleagues in Turkey. 6 In Turkey homeopathy is novel but increasing in popularity, and the subject of a new regulatory system. The Portuguese pharmacists who participated reported that they were grateful to be able to work in homeopathy and considered that specialised education was the most important factor for success; also that patients' attitudes are generally positive.…”
Section: Cross-fertilisationmentioning
confidence: 99%